Sexual Harassment, Sexual Assault, and Physical Activity Among U.S. Military Service Members in the Millennium Cohort Study - Thomas, Connie L. (Journal of interpersonal violence, 2021)
Sexual harassment (SH) and sexual assault (SA) continue to be a focus of prevention efforts in the U.S. military because of the prevalence and potential to affect the health and readiness of service members. Limited research exists on the association of SH and SA with coping behaviors, such as physical activity, within the military. Data including self-reported SA, SH, and physical activity were obtained from the Millennium Cohort Study, a longitudinal cohort study designed to examine the impact of military service on the health and well-being of service members. A hierarchical regression approach was applied to examine the association between SH or SA and subsequent physical activity levels. Hierarchical regression showed that, among those self-reporting recent SA, the odds of medium-high (300-449 min/week) and high physical activity levels (≥450 min/week) were significantly increased. Although the magnitude of these associations was attenuated with an increasing amount of adjustment, the odds of high physical activity levels remained statistically significant in the fully adjusted model (medium-high: odds ratio [OR] = 1.72, 95% confidence interval [CI] = [1.08, 2.73]; high: OR = 1.58, 95% CI = [1.02, 2.44]). We observed statistically significant negative associations between recent SH and medium-high physical activity levels in adjusted models (OR = 0.70, 95% CI = [0.54, 0.91]). The current results demonstrate that SA is generally associated with increased levels of physical activity among military service members. Analyzing the relationship between sexual trauma and physical activity is valuable because of the high prevalence of SH and SA in the military, long-term health implications including physical and emotional well-being, and potential impact on military readiness.